IMPROVEMENT OF THE PEDAGOGICAL MECHANISM FOR DEVELOPING THE PROFESSIONAL AND ETHICAL OUTLOOK OF FUTURE TEACHERS - Djumayeva Sanobar Absaatovna (The Bioscan, 2024)
This article explores the improvement of the pedagogical mechanisms aimed at developing the professional and ethical outlook of future teachers. In today’s rapidly changing educational landscape, teachers must possess not only academic expertise but also a strong ethical foundation to guide students both intellectually and morally. The article addresses the current challenges in teacher education, such as inconsistent pedagogical approaches, lack of practical experience, and inadequate mentorship. Key strategies for enhancing teacher training programs are proposed, including the integration of ethics into curricula, the use of real-world case studies, and the promotion of reflective practices. Additionally, the importance of mentorship, collaborative learning, and continuous professional development is emphasized. The article concludes by recommending structural improvements to teacher education, ensuring that future educators are well-prepared to meet the professional and ethical demands of their role in shaping future generations. This study contributes to the ongoing discourse on the vital role of ethical education in teacher training and presents practical solutions to improve the professional and moral competence of future teachers.